(3SbW GdRfQs - (3CMeO Hf YHO Gddg Hf SdjeGf GdJfhNj , CHh GdYdGA GdeYQj , J (B449 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3CeG HYO (B: (3aEf GdTYQGA cCaQGS JJGHYJ ai eOi , eG bUO efgG dMb , heG hba efgG dje hSHb hbO cfJ ai QHGf GdMOGKI s
(3BNQgG (B:s
(3Ke SbW GdRfQ Sei HPdc dCfg Ghd eG jNQL ef fGQg hgPG bjd ai UOQ GdYeQ s
(3GdfSNI HgG MhGTs
(3GdfSNI ebGHdI hHMhGTjgG TQhMs
(3HGdeYgO fSN CNQi GfXQ ai GdLRA GdChd GdCQbGe (B275(3,(B488(3,(B532(3,(B533(3, (B534 (3COH , hQO CjVkG Qbe (B"1717"s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs